KEWENANGAN PPNS DALAM PENYIDIKAN TINDAK PIDANA MONEY LAUNDERING TERKAIT PUTUSAN MAHKAMAH KONSTITUSI (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2022)
The Crime of Money Laundering (TPPU) is one of the criminal acts that is relatively new and interesting to review. Discussing money laundering offenses means having to discuss predicate crimes. The Crime of Money Laundering (TPPU) or better known as money laundering is a further criminal act or layering crime. The predicate offense is referred to in Article 2 paragraph (1) of Law Number 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering (PPTPPU). In the explanation of Article 74 of the PPTPPU Law as conditional constitutional, the explanation interprets the phrase